IMPACT OF TECHNOLOGICAL READINESS ON ADOPTING ARTIFICIAL INTELLIGENCE IN ACCOUNTING - Al Bari, Huzaifa Mahmood; Křivanec, Oto; Kmoch, Štěpán; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2021)
This Master’s Thesis is focused on Artificial Intelligence in Accounting in terms of the changing environment, increasing challenges, automation and the Technological readiness of Accounting Students and Entry-Level Accountants who are the target population of the study. This quantitative correlation study was conducted to find the relationship between the technological readiness and technological adoption of Artificial Intelligence enabled technologies in accounting and auditing which is vital in coping with the challenges posed by changing environment. The study was conducted in regards to the TR and TA perseverance of accounting students and entry-level accountants, of which the respondents were (n=104) which consisted of Bachelor level, Masters and PHD level accounting students from Prague University of Economics and Business and entry level accountants from DXC Technology shared service center in Prague. The participants were presented with a questionnaire survey through google forms online platform. Using the forms of analysis such as bivariate correlation and linear regression it was concluded that TR, PU and PEOU have a positive influence in the TA of A.I. by accounting students and entry-level accountants and that TR positively impacts PU and PEOU.
Vedoucí práce: Oto Křivanec
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses